Tempo e bem estar: an argument for a temporal bill of rights (Revista Estudos Culturais, 2015)
This paper examines the impact of temporal experience—time use, conceptions of time and temporal norms—on happiness and well-being and suggests public policies to enhance these experiences. First, it reviews literature concerning the interrelationships of time, money and happiness. Second, it reviews data and issues concerning the use of work and non-work hours around the world. Third, it describes a broader range of temporal issues to be considered in policymaking decisions, e.g. clock versus event time-keeping, monochronic versus polychronic approaches, the definition of wasted time, the pace of life, and temporal orientation. Finally, suggestions are of ered for the formulation of time-use policies intended to increase individual and collective happiness. It is a virtual truism that the way we use our time is the way we live our lives. Our time is our most valuable possession. Much of this time, however, is controlled by others, ranging from our employers to our closest family members. It is also clear that there are profound dif erences-- individual, socio-economic, cultural and national--in the degree to which people hold control over their own time (e.g., LEVINE, 1997; LEE, et al., 2007). It may be argued that public policies are needed to protect the “temporal rights” of individuals, particularly those who are most vulnerable to exploitation. This paper was sparked by an ambitious large-scale project in which I had the opportunity to participate. The project was initiated in the Spring of 2012 following a United Nations resolution, adopted unanimously by the General Assembly, placing “happiness” on the global agenda. The nation of Bhutan was asked to convene an interdisciplinary group of international “experts” to craft recommendations for policies to raise worldwide happiness; more specifically, to develop a “new paradigm for world development.” Bhutan, a small, landlocked, relatively poor Himalayan nation, was chosen for this task because of its pioneering Gross National Happiness (GNH) project. “Progress,” the GNH designers declared, “should be viewed not only through the lens of economics but also from spiritual, social, cultural and ecological perspectives.” Happiness and development, in other words, depend on more than growth and the accumulation of money. England, Canada and other countries and country-level organizations have subsequently followed Bhutan’s lead and established GNH measures of their own (LEVINE, 2013). One of the nine core domains of Bhutan’s GNH index is “time use,” which comprised my section of the report. The present paper draws heavily on that report and the insights that research of ered me. I will address four major sets of issues: I. The inter-relationships of time, money and happiness. Most importantly, what is the relevance of time use to well-being and happiness? II. Time Use: Work hour issues and policies. III. Other temporal factors that need to be considered when formulating policies to increase happiness. IV. Suggestions for policymaking: The call for a “Temporal Bill of Rights.”